Scaling artificial insemination adoption through support for Vietnam's service providers and farmers - Son La Sub-department of Animal Health; International Livestock Research Institute (International Livestock Research Institute, 2024)
The CGIAR Initiative on Sustainable Animal Productivity (2022–2024) focuses on improving livestock productivity and sustainability in Son La Province, Vietnam. The project promotes artificial insemination (AI) for cattle and pigs, benefiting both farmers and AI service providers. It has trained 435 participants (39% women), in breeding and AI techniques. The project also introduced a cooperative model for AI services, providing technical training, business skills and tools like liquid nitrogen storage for semen. In 2023, AI led to a 46% pregnancy rate in cows, improving livestock quality, disease resistance and farm productivity. The project has connected AI providers with farmers, enhancing access to modern techniques and improving incomes. Local authorities plan to incorporate these results into provincial livestock policies.